Enhancing Leaf Flavonoid Production in Indian Camphorweed (Pluchea indica Less.) through the Provision of Chicken Manure - Indriani, Yulia; Aziz, Sandra Arifin; Melati, Maya (Department of Agronomy and Horticulture, IPB University, 2024)
Indian camphorweed (Pluchea indica Less.) leaves exhibit antioxidant, antibacterial, anti-inflammatory, and antimicrobial activities, indicating significant potential for the pharmaceutical industry. This research aimed to determine the optimal rates of chicken manure for enhancing leaf and total flavonoid production in Pluchea indica. The study took place at the IPB Experimental Station in Bogor, Indonesia,spanning from July to October 2023. A completely randomized block design with a single factor (chicken manure doses) was employed: 0, 2.5, 5, or 7.5 kg per plant. Each treatment comprised three replications, each consisting of 20 plants. The results revealed that the application of chicken manure at 2.5 kg per plant led to significantly taller plants, more leaves, and tertiary branches compared to the control group. Specifically, the 2.5 kg dosage significantly increased the nitrogen content of the 7th leaf and the potassium content of the 3rd leaf. Meanwhile, the application of 5 kg of chicken manure per plant significantly boosted phosphorus content in the 3rd and 7th leaves and potassium content in the 5th and 7th leaves. However, no significant differences were observed in total flavonoid and antioxidant activity across all leaf positions with chicken manure application. Plants receiving 5 kg of manure demonstrated the highest fresh leaf weight (81.64 g) and dry weight (38.27 g), which were significantly greater than those receiving 2.5 kg per plant or no manure. Despite these variations, flavonoid production per plant did not show a significant difference with manure application.